Efektivitas Pelaksanaan Pemberhentian Kepala Desa Menurut Undang-Undang Tentang Desa - Nurul Muammar; Ade Darmawan Basri (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
This study is entitled Effectiveness of Village Head Dismissal According to Law Number 6 of 2014 concerning Villages (Case Study of Bontosunggu Village, Bontoharu District, Selayar Islands Regency) which aims to determine the reasons for dismissing and how to implement the dismissal of the village head in Bontosunggu Village, Bontoharu District, Selayar Islands Regency. The type of research used is juridical-empirical research, in other words, sociological legal research and can also be called field research, which examines applicable legal provisions and what happens in reality in society. The results of this study indicate that, the reason for the frequent dismissal of the Village Head in Bontosunggu Village, Bontoharu District, Selayar Islands Regency is the first to die. Because the deaths that came unexpectedly made one factor into the vacant position in the village government which ended in dismissing and appointing a new village head to fill the void. And the second is the misuse of village funds, which sees the village budget which is quite a lot to make some people tempted to use every budget that goes to the village for personal interests and benefits which can have a negative impact on state finances, especially villages. And to achieve the effectiveness of a law, of course, requires awareness of the parties who will carry out each of these statutory regulations. For example, in the case of dismissing the village head, which of course cannot be stopped arrogantly, but has been regulated in statutory regulations and several other regulations such as regional regulations, domestic ministerial regulations and other regulations. In the statutory regulations, the procedure for dismissing the village head has been explained, starting from reporting to examining the village head concerned before it is decided to be dismissed.